Nicorandil prior to primary percutaneous coronary intervention improves clinical outcomes in patients with acute myocardial infarction: a meta-analysis of randomized controlled trials [Letter] - Li J; Zhang L; Lu A (Dove Medical Press, 2019)
Jun Li, Ling Zhang, Aixia LuDepartment of Cardiology, The Second Clinical Medical College of Jinan University, Shenzhen People’s Hospital, Shenzhen 518020, People’s Republic of ChinaEarly myocardial revascularization by the primary percutaneous coronary intervention (PPCI) was an important treatment for patients with ST-segment elevated myocardial infarction (STEMI); thus, a proportion of STEMI subjects still have impaired cardiac function and increased cardiovascular mortality.Recently, we read with great interest the study by Xu et al.1 The authors performed a meta-analysis to evaluate the effectiveness of the administration of nicorandil during percutaneous coronary intervention in patients with acute myocardial infarction. They concluded that periprocedural nicorandil improves coronary blood flow, cardiac systolic function and prognosis in STEMI patients receiving primary PCI. The research appears informative clinically. Thus, we addressed some issues regarding this study.View the original paper by Li Xu and colleagues